In Vitro Comparison of Three Dimensional Cone Beamed Dental Tomography with Intraoral Radiography in Detection of Dental Root Factures - Akleyin, Ebru; Yavuz, Izzet (Journal of Dentistry Indonesia, 2019)
The precise diagnosis of dental root fractures in clinical practice is quite difficult. The aim of this study is to compare the results of three dimensional cone beam computed tomography (CBCT) and conventional intraoral radiography images in the diagnosis of dental root fractures. 50 maxillar central teeth with healthy roots were shot in a single blow in laboratory environment for cracks were studied for 10 teeth and horizontal root fractures created for 40 teeth. Parts of root fractures were sticked together by forming root fractures in five groups as crack, fracture without gap and fracture with 0,2 mm, 0,4 mm and 0,6 mm gaps. Images of all teeth were taken with CBCT and conventional intraoral radiography. Accurate diagnosis averages and positive predictive value test calculated through the data taken from the evaluation results of 30 dentists. Generally the results showed that images taken by the CBCT are better than images taken by the periapical radiography which obtained with traditional methods for the diagnosis of root fractures and cracks. The results also showed that the quality of the images increased as the voxel of the CBCT images decreased. It is shown that images taken by the CBCT provides better and clearer than the images taken by the traditional intraoral radiography in order to diagnose root fractures and cracks.